PEMBUATAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA PT.TAINAN ENTERPRISES INDONESIA - Kusnarto, Ilsan (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Founded in August 1961, Tainan Enterprises Co., Ltd. is a professional garment OEM manufacturer. The main products include: pants, shirts, dresses, skirts, jackets, vests, and coats. Tainan Enterprises initially engaged in low-end and middle-end garments of K-mart and other discount stores. In 1995, it entered the market of middle-end and high-end garments after accepting orders from Conex. Currently, the company’s main clients include: GAP, MAST, Ann Taylor, Macy’s, Talbots, and other middle-end and high-end casual apparel retailers. At present, Tainan Enterprise’s Tainan Plant is the product design center and it is the production base of high-end products. In addition, the processes and management in Taiwan have been transferred to overseas production bases, including Indonesia, China, and Cambodia. In addition to the progressive internalization of the production base, the company has also actively developed its own brand. In 1999, Tainan Enterprises (Cayman) Co., Ltd. was established, which is the holding company for the development of private labels. To date, About men's and women's wear there are near to 200 sales locations in China.